Enterprise resource planning (ERP) application : a case study of a local construction company - Dnyandeo Dadarao, Gaikwad (2008)
In today's dynamic and turbulent business environment, there is a strong need for the organizations to become globally competitive. The current approach to competitiveness is to be closer to the customer and deliver value added product and services in the shortest possible time. This is achievable through the integration of business processes of an enterprise. Enterprise Resource Planning (ERP) is such a strategic tool, it helps to gain competitive edge by integrating all business processes and optimizing the resources available.